Less is more: a rationalization of daily labwork - Chan, Barry; Nazerali-Maitland, Alasdair; Hopman, Wilma; Zelt, David; Morton, Ross (Canadian Medical Education Journal, 2018)
Routine daily phlebotomy can often act as a replacement for direct patient care. Some tests are necessary to gauge treatment response, however many are unnecessary and increase a patient’s risk of complications and can impede laboratory processing times. This study addresses the effects of providing resident trainees, who often lack an understanding of the financial impact of the tests they order, with summative feedback. This encouraged them to be resource-conscious. Internal Medicine teams were provided with weekly laboratory spending reports and this resulted in a 33% reduction in Per Person Per Day spending. No changes in mortality were noted.